2011
DOI: 10.3747/co.v18i1.647
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangitic Metastasis of Recurrent Renal Cell Carcinoma to the Contralateral Lung Causing Lymphangitic Carcinomatosis and Respiratory Symptoms

Abstract: 3.8 g/dL. Erythrocyte sedimentation rate (esr) and C-reactive protein (crp) were never measured.On current presentation, the patient also complained of fatigue and decreased appetite, and denied fevers, chills, nausea, vomiting, diarrhea, and constipation. Respiratory exam revealed decreased right lower lobe breath sounds and moderate crackles in the right middle lobe. Laboratory studies were consistent with his postoperative baselines: bun 25 mg/dL, scr 1.4 mg/dL, sCa 8.8 mg/dL, wbcs 7300/μL, hemoglobin 9.5 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…The incidence of GI metastasis is much lower than that of peritoneal metastasis and the GI tract is generally considered a late metastatic site, so it was not surprising that peritoneal seeding was accompanied by significant metastatic GI involvement. No patient was found to have regional lymph node metastasis, which stands in contrast with the result of previous studies that reported the lymphatics as the major routes for RCC spread ( 26 27 ). Our findings suggest that RCC metastasized to the GI tract through hematogenous or peritoneal seeding and not lymphatic dissemination.…”
Section: Discussioncontrasting
confidence: 99%
“…The incidence of GI metastasis is much lower than that of peritoneal metastasis and the GI tract is generally considered a late metastatic site, so it was not surprising that peritoneal seeding was accompanied by significant metastatic GI involvement. No patient was found to have regional lymph node metastasis, which stands in contrast with the result of previous studies that reported the lymphatics as the major routes for RCC spread ( 26 27 ). Our findings suggest that RCC metastasized to the GI tract through hematogenous or peritoneal seeding and not lymphatic dissemination.…”
Section: Discussioncontrasting
confidence: 99%
“…RCC metastasis usually occurs through hematogenous spread to the lung parenchyma and less frequently involves the lymphogenous route (38). Therefore, we sought to determine whether the decreased metastasis we observed upon NRP-2 knockdown was the result of reduced blood or lymphatic vessels in the primary tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Other neoplasms are rare causes of PLC [9]. In general, it is observed in about 8% of cases, mostly in adults aged 40-49 [10]. In some cases, PLC may precede or be present at the time of the initial diagnosis of the neoplasm.…”
Section: Discussionmentioning
confidence: 99%